2020
DOI: 10.1016/j.omtm.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Klotho Improves Hepatic Glucose and Lipid Homeostasis in Type 2 Diabetes

Abstract: Type 2 diabetes (T2D) is one of the most escalating global metabolic diseases, which is highly associated with insulin resistance (IR) and risk of combination with nonalcoholic fatty liver disease (NAFLD). Previous studies suggest that soluble klotho (sKL) could serve as a circulating hormone to mediate energy metabolism, but the detailed mechanism is poorly understood. In this study, we generated T2D models of wild-type (WT), sKL heterozygous ( KL +/− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 40 publications
4
29
0
Order By: Relevance
“…sKL inhibits insulin growth factor 1 receptor (IGF-1R)/phosphoinositide 3-kinase (PI3K)/AKT serine/threonine kinase (AKT) signaling and activates forkhead box O (FOXO) ( Kurosu et al, 2005 ; Yamamoto et al, 2005 ). It increases glucose uptake and glycogen storage and reduces lipid accumulation and insulin resistance through PPARα expression ( Gu et al, 2020 ) corroborating the role of KL and underlying signaling in glucose metabolism and adipocyte maturation as discussed recently ( Razzaque, 2012 ). Other KL downstream effects are the activation of extracellular signal–related kinase 1/2 (ERK1/2) ( Maekawa et al, 2011 ), inhibition of Wnt signaling ( Liu et al, 2007 ), or reduction of inflammation ( Maekawa et al, 2009 ).…”
Section: αKlothosupporting
confidence: 70%
“…sKL inhibits insulin growth factor 1 receptor (IGF-1R)/phosphoinositide 3-kinase (PI3K)/AKT serine/threonine kinase (AKT) signaling and activates forkhead box O (FOXO) ( Kurosu et al, 2005 ; Yamamoto et al, 2005 ). It increases glucose uptake and glycogen storage and reduces lipid accumulation and insulin resistance through PPARα expression ( Gu et al, 2020 ) corroborating the role of KL and underlying signaling in glucose metabolism and adipocyte maturation as discussed recently ( Razzaque, 2012 ). Other KL downstream effects are the activation of extracellular signal–related kinase 1/2 (ERK1/2) ( Maekawa et al, 2011 ), inhibition of Wnt signaling ( Liu et al, 2007 ), or reduction of inflammation ( Maekawa et al, 2009 ).…”
Section: αKlothosupporting
confidence: 70%
“…CSF α-Klotho’s prominent role in energy balance was demonstrated by strong inverse correlations with body weight and an ability to increase energy expenditure [ 20 ]. Soluble Klotho improves hepatic glucolipid homeostasis to ameliorate diabetic phenotypes and lipid accumulation in the mice model with type 2 diabetes mellitus in comparing wild-type, soluble Klotho heterozygous, and soluble Klotho transgenic group [ 21 ]. Histological examination suggests that Klotho mice possess less energy storage than wild-type mice concerning glycogen in the liver and lipid in brown adipose tissue [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the overexpression of sKL reversed these phenomena. 37 Rao et al found administration of Klotho resulted in decreased fat mass, increased lean mass and reduced lipid accumulation in liver of obese mice. 35 In addition to hepatic lipid accumulation, insulin resistance also plays a crucial role in fatty liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…45 Moreover, PPAR-α was also reported to mediate the regulation of sKL on hepatic lipid metabolism in mice. 37 Genetic polymorphisms of Klotho gene were associated with various pathophysiological processes and diseases. [10][11][12][13] In our Chinese cohort, carriage of the KL rs495392 A allele was related to a lower risk of severe steatosis in patients with NAFLD, without affecting body mass nor insulin resistance.…”
Section: Discussionmentioning
confidence: 99%